The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1002/ajim.4700270303
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of risk of developing bladder cancer among workers exposed to coal tar pitch volatiles in the primary aluminum industry

Abstract: To confirm the relationship between exposure to coal tar pitch volatiles and bladder cancer among primary aluminum production workers, we carried out a case-control study among blue-collar workers who had worked more than 1 year between 1950-1979 in a major plant using mostly the Soderberg process in the Province of Québec. Cases of bladder cancer (ICD code 188) diagnosed between 1970-1979 (n = 69) were mostly included in a previously reported study. To these were added cases diagnosed between 1980-1988 (n = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
51
3
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 12 publications
4
51
3
1
Order By: Relevance
“…Unlike most studies in the aluminum industry, we did not find an association between bladder cancer and work in the aluminum industry (8,(16)(17)(18)(19). Perhaps the absence of any association is due to smoking, which implies that the real risk of lung cancer would be higher than observed in our study if we had been able to control for smoking.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Unlike most studies in the aluminum industry, we did not find an association between bladder cancer and work in the aluminum industry (8,(16)(17)(18)(19). Perhaps the absence of any association is due to smoking, which implies that the real risk of lung cancer would be higher than observed in our study if we had been able to control for smoking.…”
Section: Discussioncontrasting
confidence: 97%
“…Friesen et al (14) found a moderate association between exposure to PAH and acute myocardial infarction for aluminum smelter workers. As regards the incidence of cancer, the most consistent finding in previous studies has been an increased incidence of bladder cancer (8,(14)(15)(16)(17)(18)(19)(20). Cancer of the lungs (11,14,17,21,22) , pancreas (18), kidneys (15,17,18), lymphoma (17), stomach (17), and brain (23) has also been found to be associated with workers in aluminum plants, but these findings are less consistent.…”
mentioning
confidence: 94%
“…Tobacco smoking did not confound the relationship. Tremblay et al (1995) expanded the previous study and included 138 cases of bladder cancer, 66 cases of the previous study, 69 cases diagnosed between 1980 to 1988 and three additional cases diagnosed before 1980. Three matched controls were taken from the previous studies or selected from a subcohort of 1138 men enumerated by Armstrong et al (1994, see below) drawn mainly from the same subcohort.…”
mentioning
confidence: 99%
“…Further support for PAH carcinogenicity in humans has been provided by epidemiologic studies such as those carried out in aluminum workers of the Saguenay-Lac Saint-Jean region of Canada (6)(7)(8). In these studies, the epidemiologic association between exposure to PAHs and lung and urinary bladder cancers has been strong enough to warrant the compensation of affected workers by the Quebec Health and safety Workers Compensation Board (6)(7)(8).…”
mentioning
confidence: 99%
“…In these studies, the epidemiologic association between exposure to PAHs and lung and urinary bladder cancers has been strong enough to warrant the compensation of affected workers by the Quebec Health and safety Workers Compensation Board (6)(7)(8).…”
mentioning
confidence: 99%